35 Endoscopic vein harvest: early experience of adopting a minimally invasive conduit harvesting technique. (16th October 2019) - Siddiqui, S; DaCosta, M; Veerasingam, D; Bartolozzi, F; Soo, A
Abstract : Introduction: Despite multiple randomized trials, coronary artery bypass grafting (CABG) remains the gold standard revascularisation technique for severe coronary artery disease. The long saphenous vein (LSV) is the most common conduit used due to its abundant length and ease of harvest. Traditionally, LSV is harvested using an open technique. However, the open technique is associated with severe wound complications and poor cosmesis. Endoscopic vein harvesting (EVH) is a new minimally invasive vein harvesting technique with significant advantages. This technique was introduced in UHG on February 2017. Here we report our early experience of adopting this technique. Aim: To assess the impact of EVH during our early experience. Method: Data was obtained retrospectively from a prospectively maintained electronic database of all CABG patients from February 2017 to February 2019. Data analysis was performed using MS Excel. Results: From February 2017 to February 2019, 207 patients underwent CABG procedure that required at least one LSV graft. 118 patients (57%) underwent EVH. During our early experience, the average harvesting time per vein graft length was 35 minutes for the first 10 cases. This improved significantly with experience with the average harvesting time per vein graft length now being 15 minutes. There was negligible blood loss in all cases. There were 5 conversions (4%) to open LSV harvesting, due to bleeding. There was no conversion in last 58 cases. Post operatively, average pain score was 1/10. 5 patients (4.2%) developed haematoma at the LSV harvest site, which did not require intervention. There were no late wound complications. In contrast, during the same period, 5 patients who had open LSV harvest, developed severe surgical site infection. Conclusion: EVH, although challenging, could be introduced safely with appropriate mentoring. The adoption of EVH has significantly improved wound infection rate in patients undergoing CABG in our experience.